Argumentation in Multi-Agent Systems 7th International Workshop, ArgMAS 2010 Toronto, ON, Canada, May 10, 2010 Revised, Selected and Invited Papers - McBurney, Peter; Rahwan, Iyad.; Parsons, Simon; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly reviewed post-proceedings of the 7th International Workshop on Argumentation in Multi-Agent Systems, ArgMas 2010, held in Toronto, Canada in May 2010 as a satellite workshop of AAMAS 2010. The 14 revised full papers taken from ArgMAS 2010 were carefully reviewed and improved during two rounds of revision. Also included are 4 invited papers based on presentations on argumentation at the AAMAS 2010 main conference. All together the 18 papers included in the book give a representative overview on current research on argumentation in multi-agent systems. The papers are organized in topical sections on practical reasoning and argument about action, applications, and theoretical aspects.
Keywords: Computer science; Computer Communication Networks; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Mathematical Logic and Formal Languages; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction